Shared symmetries of the hydrogen atom and the two-bit system. (21st November 2017) - Rau, A R P; Alber, G
Abstract: The hydrogen atom is the simplest system of atomic and molecular physics, while a two-qubit system is the simplest of quantum information. Remarkably, they share common symmetry aspects which are described in this paper, based on a correspondence between the four-dimensional unitary group and the six-dimensional rotational group with its non-compact extensions. Both systems involve 15 basic operators. Reductions to Lorentz and Poincare space–time group symmetries of a free particle are also discussed.